Critical Study and Performance Improvement of the Drive Systems for a Class of Machine Tools - Mikho Mikhov; Marin Zhilevski (Advanced Aspects of Engineering Research Vol. 1, 2021)
This paper deals with some problems in the modernization of a type of machine tools with multi-coordinate drive systems. Machine tools are used for processing of workpieces with various geometrical shapes. The basic requirements to the drives of each coordinate axis and the spindle are presented. Using the analysis carried out, a practical approach to appropriate selection of the respective drives is applied. The methodology offered is illustrated with some examples for choice of drives with direct current and alternating current motors. Some experimental research of cases with different feed and spindle drives are described and discussed. Better capabilities of the modernized machines for processing more complex workpieces are achieved, at a relatively low price. This research and the obtained results can be used in the design and tuning of electric drives for the considered type of machines with numerical program control.